2005
DOI: 10.1525/can.2005.20.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Doctors, Borders, and Life in Crisis

Abstract: The politics of life and death is explored from the perspective of Doctors Without Borders (Médecins sans frontières [MSF]), an activist nongovernmental organization explicitly founded to respond to health crises on a global scale. Following the work of Michel Foucault and Giorgio Agamben, I underline key intersections between MSF's operations that express concern for human life in the midst of humanitarian disaster and the group's self‐proclaimed ethic of engaged refusal. Adopting the analytic frame of biopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
188
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(193 citation statements)
references
References 41 publications
(9 reference statements)
1
188
0
4
Order By: Relevance
“…This is hardly surprising, as conflict intervention literature has long noted the necessity of restoring "legitimate and functioning order and authority" as well as stopping atrocities; the latter is unsustainable without the former. 56 What RtoP offers suffering populations and individuals then is the minimalist protection that characterizes humanitarianism, 57 as opposed to the maximalist protection offered to the state. And this is a protective logic shared by the EU, both in its enlargement policy (see above) and in its immigration and asylum arrangements.…”
Section: Parallel Protection: Eu Rtop and The Statementioning
confidence: 99%
“…This is hardly surprising, as conflict intervention literature has long noted the necessity of restoring "legitimate and functioning order and authority" as well as stopping atrocities; the latter is unsustainable without the former. 56 What RtoP offers suffering populations and individuals then is the minimalist protection that characterizes humanitarianism, 57 as opposed to the maximalist protection offered to the state. And this is a protective logic shared by the EU, both in its enlargement policy (see above) and in its immigration and asylum arrangements.…”
Section: Parallel Protection: Eu Rtop and The Statementioning
confidence: 99%
“…She characterizes humanitarianism by its state-like functions, identifying a new form of sovereignty at the intersection of biopolitics and 'bare life', ultimately resulting in the reduction of subjective individuality and the influx of diagnostic and numerical categories based on humanitarian management (Pandolfi 2003, 499). 3 In subsequent years anthropologists published widely read critical studies: Redfield's (2005Redfield's ( , 2013 retrospective ethnographies of MSF, Fassin's (2012, 1-2) critique of the humanitarian epistemology of 'moral sentiments' with regards to the status of immigrants in France, and Nguyen's (2010) commentary against the unintentional making of new markets and economies among both HIV/AIDS patients and their ART therapies on the part of the 2 This is not to say that humanitarian actors and agencies themselves have not engaged in a tradition of self-critique. According to Davey and Scriven (2015, 115), medical humanitarianism 'cannot be accused of an unwillingness to reflect on its performance, be it through formal processes of research and evaluation or the collect decompression of a bar-side lament'.…”
Section: Anthropology As Critiquementioning
confidence: 99%
“…Others have observed that, although related to the boundaries of the nation-state, governmental power can be distributed across sites that extend beyond it (Ferguson and Gupta 2002;Hansen and Stepptuat 2005;Ong 1999Ong , 2006Trouillot 2001). While this literature has focused on the production of spaces of sovereign influence and intervention, another set of literature on sovereignty has studied the construction of active subjectivities within contemporary-usually neoliberalgovernmental contexts (e.g., Biehl et al 2007;Rose 1999aRose , 1999b what Agamben (1998) termed "bare life" rather than on broader conceptualizations of welfare (Comaroff 2007;Fassin 2007;Petryna 2002;Redfield 2005). This literature has explored cases of people making claims to resources on the basis of their entitlement to survive rather than other kinds of rights, such as the right to work, have a family life, or join political associations (Nguyen 2005(Nguyen , 2010Ticktin 2006).…”
Section: The Organization That Employed This Young Man Was the Us Mmentioning
confidence: 99%
“…PEPFAR organizations acted primarily through humanitarian rationalities based on a sense of moral obligation to intervene in the lives of a section of the population-those living with or at risk of HIV/AIDS-rather than the whole population, within a context of doubt about state capacity to provide services to its citizenry (cf. Lakoff 2010;Redfield 2005Redfield , 2012. Their activities played out within the broader context of a developmental rationale that has historically based understandings of the need for intervention on representations of failure and weakness (Escobar 1995;Ferguson 1990;Li 2007).…”
Section: Geissler and Prince 2010)mentioning
confidence: 99%